2019
DOI: 10.1002/cctc.201900393
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Oxalamide Ligand for Copper‐Catalyzed C−O Couplings from a Pharmaceutical Compound Library

Abstract: Figure 1. Strategy for using the AbbVie compound library as a source for identification and design of new ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In this case, shifting the carbonyl group toward the periphery completely eliminated the reactivity. This suggests that maintaining a carbonyl for binding as a five-membered chelate in the catalytic cycle is important. , From a further survey of ligands, it became apparent that the catalyst maintained high activity when binding as a chelate through nitrogen, preferably through two amides. Regarding the ligands designed by Ma’s group, the oxalamide moiety was the most critical design element.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, shifting the carbonyl group toward the periphery completely eliminated the reactivity. This suggests that maintaining a carbonyl for binding as a five-membered chelate in the catalytic cycle is important. , From a further survey of ligands, it became apparent that the catalyst maintained high activity when binding as a chelate through nitrogen, preferably through two amides. Regarding the ligands designed by Ma’s group, the oxalamide moiety was the most critical design element.…”
Section: Resultsmentioning
confidence: 99%
“…This Ni/ligand combination also enabled the coupling of secondary-heteroatom-containing alkyl bromides with aryl bromides in synthetically useful yields. This report nicely illustrates the utility of mining pharmaceutical compound libraries to identify ligands for challenging transformations …”
Section: Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 72%
“…This report nicely illustrates the utility of mining pharmaceutical compound libraries to identify ligands for challenging transformations. 11 Following their impressive work using pyridine carboxamidines as effective ligands for Ni-catalyzed reductive couplings, Weix and co-workers have reported that pyridine-2,6-bis(Ncyanocarboxamidine) (PyBCam CN ) is an effective ligand for coupling of aryl chlorides with primary alkyl chlorides (Scheme 3). 12 The authors have noted that in addition to the fact that organochlorides are more abundant than organobromides and iodides, the inertness of the C−Cl bond allows this functional group to be introduced early in the synthesis for late-stage manipulations.…”
Section: ■ Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%
“…The catalytic system containing the oxalamide, L20 , reported by Ma for the synthesis of alkyl aryl ethers, [16] afforded low yield of the product at the catalyst loading of 0.05 mol % with K 3 PO 4 base. Another catalytic system containing oxalamide ligand L21 , which was recently reported by a team of scientists at AbbVie, [15c] gave high yield of the product (78 %) at the higher catalyst loading but gave low yield at the lower loading of 0.0125 mol %. Likewise, the catalysts containing oxalamides L22 – L24 formed the biaryl ether at 0.05 mol % catalyst, but did not form the biaryl ether in high yield with the lower loadings suitable for catalyst containing the ligands in this work.…”
Section: Resultsmentioning
confidence: 95%